Compositional-driven multiferroic and magnetoelectric properties of NdFeO3-PbTiO3 solid solutions. Issue 1 (2nd January 2021) - Kumar, Sunil; Aggarwal, Kanika; Pal, Jaswinder; Kaur, Shubhpreet; Arora, Mehak; Malhi, Parambir Singh; Babu, P. D.; Singh, Mandeep; Singh, Anupinder
ABSTRACT: Synthesis of polycrystalline (Pb1- x Nd x )(Ti1- x Fe x )O3 (for x  = 0.21–0.30) solid solutions using solid-state reaction method has been reported. The structural, dielectric, ferroelectric, magnetic, and magnetoelectric properties of the resulting solid solutions have been investigated in detail. The XRD data show that the phase transition occurs at 0.27 ≤  x  ≤ 0.28 at room temperature. The dielectric studies show that the transition temperature continuously decreases with increasing " x ". So it is clearly evident from XRD and dielectric data that the tetragonal to cubic phase transition occurs at x  = 0.27 to x  = 0.28 at room temperature. The remnant polarization (Pr ) decreases from 19.78 μC/cm 2 to 11.13 µC/cm 2 gradually up to x  = 0.25 whereas other samples exhibit lossy behavior. The remnant magnetization (Mr ) continuously increases from 0.068 emu/g to 0.467 emu/g with composition. All samples exhibit a positive magnetoelectric effect which is the strongest in x  = 0.22 sample.